Pelatihan Kewirausahaan Home Care Kebidanan bagi Alumni Jurusan Kebidanan - Fithriany Fithriany; Juliastuti Juliastuti; Nurbaiti Nurbaiti; Yulia Fitri; Putri Santy; Irma Seriana; Cut Yuniwati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Home care-based midwifery services have considerable economic and social potential; however, many midwifery graduates still face challenges in developing sustainable independent businesses. This community service program aimed to enhance the entrepreneurial competencies of midwifery alumni in managing home care businesses through a two-day intensive training program. The training methods included lectures, interactive discussions, case studies, role-playing simulations, and direct field observation at a partner independent midwifery practice (PMB). The training materials covered business needs assessment, service package development and pricing strategies, professional communication, financial management, strategies for obtaining start-up capital, and the preparation of simple business plans. A total of 20 alumni from the Midwifery Department of Poltekkes Kemenkes Aceh participated in the program. Evaluation was conducted using pre-test and post-test assessments. The results showed that the average participant score increased from 39.8% to 81.7% after the training. Improvements were observed across all measured competencies, indicating the effectiveness of the program in enhancing participants’ knowledge of home care midwifery entrepreneurship. Participants also gained practical skills in developing simple business plans and identifying strategies to acquire their first clients. This program is expected to contribute to the emergence of new independent entrepreneurs and support the improvement of maternal and child health services through affordable and high-quality home care services.